Maintenance of the Self-Reported Behavior Change Stage Among Male Bus Drivers Using Longitudinal Occupational Health Checkup Data: Retrospective Cohort Study - Eiko Nakanishi; Reiko Sakashita; Masakazu Morimoto; Manabu Nii (Asian/Pacific Island Nursing Journal, 2026)
Abstract Background Public bus drivers experience prolonged sitting, irregular shifts, limited breaks, and disrupted meals and sleep, making the maintenance of a healthy lifestyle difficult. Although occupational health checkups identify health risks, little is known about the duration of maintenance of self-reported stages of behavior change or their association with physiological markers. Objective This study examined the duration of maintenance of the self-reported stage of behavior change and its association with physiological markers and lifestyle behaviors among male bus drivers. Methods This retrospective cohort study analyzed occupational health checkup data collected from male bus drivers at a passenger bus company in Japan between 2006 and 2023. The primary exposure was the self-reported behavior change stage, based on a standard questionnaire item used in the Specific Health Checkups questionnaire. For the duration analysis, each participant’s longest continuous action or maintenance episode was identified, and the Kaplan-Meier analysis was used to estimate the retention time. For the outcome analyses, participants who maintained the action or maintenance stage for at least 1.5 years after time 0 were classified as the sustained group. Those who returned to the preaction or preparatory stage at 6 months or 1 year comprised the comparison group. Physiological markers were compared using analysis of covariance adjusted for baseline values, age, and medication use. Lifestyle items were analyzed using multivariable logistic regression. Results The survival analysis dataset included 717 participants, of whom 566 (78.9%) returned to the preaction or preparatory stage, while 151 (21.1%) were right-censored. The mean age at the start of the maintenance episode was 47.2 (SD 7.0) years, and the median retention time was 362 (IQR 0-1087) days. Retention probabilities were 57.7% at 6 months, 44.1% at 1 year, 33.3% at 2 years, and 23.2% at 3 years. In the outcome analyses, the sustained and comparison groups included 249 and 468 participants, respectively. At baseline, waist circumference was lower in the sustained group (85.77 cm vs 87.54 cm; P =.02), whereas other markers and medication use did not differ significantly between groups. At 2 and 3 years, the sustained group had lower BMI, waist circumference, triglycerides, and higher high-density lipoprotein cholesterol levels. Glycated hemoglobin (HbA 1c ) levels were lower in the sustained group at 3 years ( P =.02). The sustained group had higher odds of an exercise habit (1 year: odds ratio [OR] 3.40, 95% CI 2.24-5.16; 2 years: OR 8.90, 95% CI 5.26-15.07) and daily physical activity (1 year: OR 2.51, 95% CI 1.61-3.91; 2 years: OR 5.17, 95% CI 2.93-9.13), and lower odds of current smoking (1 year: OR 0.36, 95% CI 0.14-0.95; 3 years: OR 0.26, 95% CI 0.09-0.75). Conclusions Maintenance of the self-reported behavior change stage often began in midlife but was difficult to sustain beyond 1 year. Long-term maintenance was associated with favorable physical activity–related lifestyle patterns, lower smoking prevalence, and more favorable metabolic profiles. Health guidance should evaluate not only numerical improvements but also sustained behaviors and the prevention of worsening under occupational constraints.